Evaluation of antenna performance for use in wide band wireless protocols - Kuruvilla S., Mathew; Issac, B.; Tan, Chong Eng (Institute of Electrical and Electronics Engineers Inc., 2016)
Wideband transmission improves the ability of a device to communicate in different scenarios and with a range of devices. Wideband transmission protocols can also make use of multiple bands to implement parallelism and thereby improve throughput. Such transmissions require hardware that is capable of handling wideband signals for both, transmission and reception. The study undertaken in this paper looks at some popular antennae and their performance in wideband scenarios. It is usually noticed that high-frequency signals (mobile phones, WiFi, 3G, etc.) show very high attenuation in foliage. However, it is also noticed that lower frequencies (TV signals, FM radio, CB Radio, etc.) can penetrate the same environments quite well. Hence a wideband protocol that can adaptively use the available frequency band is needed. This paper presents the comparison of antennae that may be beneficial for use with such a protocol, in an attempt to identify a low-cost and effective antenna that will sufficiently satisfy the communication requirements for radio signals from 100 MHz to 2.4 GHz. Some available popular antennae, namely, 2.4 GHz Yagi Antenna, Whip Antenna and the retractable telescopic antenna, was considered for this study since the cost was an important criterion.